Implementasi KPR Bersubsidi Melalui Skema FLPP (Fasilitas Liquiditas Pembiayaan Perumahan) di PT. Trah Wali Nagari - Farida; Endah Tri Wisudaningsih; Waqiatul Aqidah (Jurnal Informatika Ekonomi Bisnis, 2023)
This study departs from the rapid population growth which results in high demand for livable housing, but with high house prices most people do not have the ability to buy houses with cash, in this situation people prefer to look for other ways by applying for loans through home ownership financing from financial institutions. This was also welcomed by government support in the form of Subsidized Housing Loans (KPR), one of which is provided through the Housing Finance Liquidity Facility (FLPP). PT. Trah Wali Nagari is also a company engaged in contraction and real estate services which also cooperates with banks in running their business, where the application of mortgages through the FLPP scheme can also attract customers to own housing there. This study aims to find out how the mechanism or process for implementing Subsidized KPR through the FLPP scheme at PT. Wali Nagari breed. In this study the authors used a qualitative descriptive research type. Qualitative descriptive research is research conducted to describe and interpret objects in accordance with actual facts/phenomena (factualitative). In conducting this research, the researcher strives to obtain valid and accountable data, therefore the determination of informants must be representative or representative. This research resulted in findings on how PT. Trah Wali Nagari as the Developer works closely with the implementing Bank to realize subsidized KPR assistance to Low-Income Communities (MBR) as well as the mechanism for submitting KPR through the FLPP scheme to implementing Banks as well as how to implement Subsidized KPR through the FLPP scheme at PT. Trah Wali Nagari can help low-income people.